2021
DOI: 10.1103/physrevlett.127.107201
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Crossover between Low- and High-Temperature Dynamical Regimes in the Quantum Heisenberg Magnet

Abstract: The stranglehold of low temperatures on fascinating quantum phenomena in one-dimensional quantum magnets has been challenged recently by the discovery of anomalous spin transport at high temperatures. Whereas both regimes have been investigated separately, no study has attempted to reconcile them. For instance, the paradigmatic quantum Heisenberg spin-1/2 chain falls at low-temperature within the Tomonaga-Luttinger liquid framework, while its high-temperature dynamics is superdiffusive and relates to the Karda… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
(72 reference statements)
1
8
0
Order By: Relevance
“…The spins make quantum Heisenberg antiferromagnetic spin- 1 2 chains described by Hamiltonian (1), where the exchange constant J is equivalent to ∆E. In the thermodynamic limit, there is no long-range magnetic order in them because of the Mermin-Wagner theorem 40 , but such quantum spin chains can host diffusive, super-diffusive, or ballistic spin transport, depending on the temperature and magnetization [29][30][31][32] . More importantly, if the chain length becomes finite, such as l = 30, or the magnetization is nonzero, there are nonzero spin Drude weights at finite temperature, and thus ballistic quantum spin transport can be achieved along the reconstructed edges [29][30][31][32][41][42][43] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spins make quantum Heisenberg antiferromagnetic spin- 1 2 chains described by Hamiltonian (1), where the exchange constant J is equivalent to ∆E. In the thermodynamic limit, there is no long-range magnetic order in them because of the Mermin-Wagner theorem 40 , but such quantum spin chains can host diffusive, super-diffusive, or ballistic spin transport, depending on the temperature and magnetization [29][30][31][32] . More importantly, if the chain length becomes finite, such as l = 30, or the magnetization is nonzero, there are nonzero spin Drude weights at finite temperature, and thus ballistic quantum spin transport can be achieved along the reconstructed edges [29][30][31][32][41][42][43] .…”
Section: Resultsmentioning
confidence: 99%
“…The reconstructed edges consist of carbon pentagons or a hybrid of hexagons and pentagons, and host quantum Heisenberg antiferromag-netic spin-1 2 chains. These quantum spin chains, with finite lengthes or nonzero magnetization, can be used to transfer spin information due to their super-diffusive and ballistic spin transport [29][30][31][32] . More detailed result will be presented in the following.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that nuclear spins decay by coupling to magnetic fluctuations, the rate at which nuclear spins depolarize (i.e. the T 1 time) is related as follows to the local autocorrelation function of the nearby electron spins [167,168]:…”
Section: Nuclear Magnetic Resonancementioning
confidence: 99%
“…Thus, we have shown that the configuration coherence can be efficiently computed for 1D systems with a suitable low-rank MPDO representation. Such systems include infinite size dissipative quantum chains [74], open many-body localized systems [75][76][77], strongly thermalizing systems [78], exciton dynamics [79], the quantum Heisenberg magnet [80], and temporal entanglement in many-body Floquet dynamics [81,82]. Experimentally, the configuration coherence can be obtained by estimating the purity of the mixed state [83,84] and subtracting the values encoding classical correlations; the latter are constructed out of local density measurements.…”
mentioning
confidence: 99%